Khushu’ in the Qur'an: Bridging Divine Contemplation and Spiritual Intelligence - Fatimah, Devia Siti (UIN Sunan Gunung Djati Bandung, 2025)
Inner peace is a universal aspiration, enabling individuals to navigate life with a calm and serene heart. One of the key factors influencing a person’s sense of peace or anxiety is the quality of their faith. To enhance faith, one needs a heart and mind that are constantly focused on Allah SWT, humbling oneself before Him—what is commonly referred to as solemnity (khushu’). This study aims to explore the concept of solemnity in the Qur’an using descriptive and thematic methods. The findings reveal that the meaning of solemnity in the Qur’an encompasses several aspects, including submission, lowering one’s voice and heart, as well as focus and obedience in performing good deeds. The research also identifies a connection between solemnity and spiritual intelligence, particularly through the concept of the God Spot, introduced by Ary Ginanjar in Emotional Spiritual Quotient (ESQ). The God Spot refers to the point of awareness within individuals that fosters their spiritual nature and innate urge to seek God. Applying the God Spot concept in daily life can help individuals experience God’s real presence, become a source of inner peace, and strengthen their spiritual values. This research contributes to the understanding of how solemnity can enhance one’s faith quality and inner calm through a deeper spiritual approach.